Citrulline Supplementation Induces Changes in Body Composition and Limits Age-Related Metabolic Changes in Healthy Male Rats. Issue 7 (27th May 2015) - Moinard, Christophe; Le Plenier, Servane; Noirez, Philippe; Morio, Béatrice; Bonnefont-Rousselot, Dominique; Kharchi, Caroline; Ferry, Arnaud; Neveux, Nathalie; Cynober, Luc; Raynaud-Simon, Agathe
Abstract: Background: Aging is associated with profound metabolic disturbances, and citrulline may be of use to limit them. Objective: The aim of this work was to evaluate the long-term effect of citrulline supplementation on metabolism in healthy aged rats. Methods: Twenty-month-old male rats were randomly assigned to be fed (ad libitum) for 12 wk with either a citrulline-enriched diet (1 g ⋅ kg −1 ⋅ d −1 ) or a standard diet [rendered isonitrogenous by addition of nonessential amino acids (NEAAs)]. Motor activity and muscle strength were measured, body composition was assessed, and muscle metabolism (protein structure, mitochondrial exploration, and transductional factors) and lipid metabolism (lipoprotein composition and sensitivity to oxidative stress) were explored. Results: Compared with the NEAA-treated group, citrulline supplementation was associated with lower mortality (0% vs. 20%; P = 0.05), 9% higher lean body mass ( P < 0.05), and 13% lower fat mass ( P < 0.05). Compared with the NEAA-treated group, citrulline-treated rats had greater muscle mass (+14–48% depending on type of muscle; P < 0.05 for tibialis, gastrocnemius, and plantaris). Susceptibility to oxidation of lipoproteins, as measured by the maximal concentration of 7-ketocholesterol after copper-induced VLDL and LDL oxidation, was lower in citrulline-treated rats than in NEAA-treated rats (187 ± 8 μmol/L vs. 243 ± 7 μmol/L; P = 0.0005). Conclusions: Citrulline treatment in male aged rats favorably modulates body composition and protects against lipid oxidation and, thus, emerges as an interesting candidate to help prevent the aging process.